(untitled) (Philological Studies, 2019)
The Macedonian and Turkish languages have specific characteristics in terms of syntax structures. Namely, in both Macedonian and Turkish, a constitutive part of the sentence is the predicate albeit differently positioned. The position of the predicate in Macedonian is usually in the middle of the sentence, whilst in Turkish it tends to be at the end. In most cases, the predicate is accompanied by a subject that determines the form of the predicate. The subject in both languages is usually at the beginning. Also, an essential part of the sentence is the object, which in Macedonian is usually at the end of the sentence, and in the Turkish it is in the middle. For example, in Macedonian: Јасмина наслика слика (subject: Јасмина; predicate: наслика; object: слика), and in Turkish: Yasemin resim çizdi (subject : Yasemin; object: resim; predicative : çizdi). An essential sentence part is the adjunct, which in Turkish is always placed before the predicate, and in Macedonian it depends on the type, so it can be placed both before and after the predicate.